Latin American Environmental Journals in Scopus and WoS in 2019: Relationship with Environmental Indicators - Marín Velásquez, Tomás Darío (2021)
The research aimed to analyze the ALyC journals indexed in Scopus and WoS around environmental sciences in 2019, as well as their relationship with certain environmental indicators. It was carried out with a quantitative approach and an explanatory level, based on data obtained from the official Scopus and WoS portals. The bibliometric data were the countries that have indexed journals, the Number of Journals, the Impact Factor, Number of Published Documents, Number of Citations, Number of Self-Quotations, Ratio of Citations per Document, Ratio of External Citations per Document, Percentage of International Collaboration and Quartile of location of each journal. The environmental indicators were taken from the World Bank's official website and were Energy Use, Protected Areas, PM2.5 Pollution, CO2 Emissions and Total Natural Resource Income. The statistical analyses were based on descriptive and multivariate techniques, such as cluster analysis, canonical correlations, and multivariate regression, all with a 95% confidence level. There were obtained 48 Scopus journals and 29 WoS, with Brazil, Chile, Colombia and Mexico as the countries with greater presence of magazines in the region. In the environmental indicators, Brazil and Chile stand out. The bibliometric variables that are significantly related to environmental indicators were the Number of Journals and Self-citations. The environmental indicator that is positively related to bibliometric variables was Protected Areas and negatively related to PM2.5 pollutions.